Bosutinib-Induced Pleural Effusion—Class Effect and Cross-Intolerance to All Tyrosine Kinase Inhibitors - Nikhil Vojjala; Hizqueel A. Sami; Nikhil Kumar Kotla; Supriya Peshin; Kanika Goyal; Soumya Kondaveety; Rishab Rajendra Prabhu; Geetha Krishnamoorthy (Hematology Reports)
Introduction: Tyrosine kinase inhibitors (TKIs) serve as the backbone in the management of chronic myelogenous leukemia and Philadelphia-positive Acute lymphoblastic Leukemia (Ph+ve ALL). With the growing use of TKIs, there has been an increase in adverse events related to these agents. Hereby, we present elderly women with Ph+ve ALL who developed recurrent pleural effusion, which was managed by switching the TKI and highlighting pleural effusion due to a third-generation TKI Bosutinib, adding to the minimal available literature. Case Description: Our patient is a 79-year-old female with Ph+ve ALL diagnosed in 2015 and started on treatment. She is also on TKI maintenance initially with Imatinib later shifted to second-generation TKIs. She started developing worsening dyspnea related to pulmonary toxicity related to TKI in the form of pleural effusion. Pleural effusion was initially managed with diuretics, later requiring thoracocentesis. Because of persistent pleural effusion, she was changed to multiple TKIs and finally started on Bosutinib. She even developed progressive pleural effusion while on Bosutinib which is managed by thoracocentesis. Conclusions: Through this case report, we would like to highlight refractory recurrent pleural effusion caused by bosutinib adding to the minimal available literature. In addition, we highlight the various treatment options in patients having cross-intolerance to various TKIs, especially pulmonary toxicity, and ponatinib might be a suitable option in such cases.